The Role and Engineering of DREB Genes in Improving Drought and Salinity Resistance in Plants: A Systematic Literature Review - Muarifah Muarifah; Yaumil Maghfirah Maghfirah; Yusminah Hala (BIOPENDIX, 2026)
This study aims to systematically examine the role, molecular mechanisms, and effectiveness of DREB (Dehydration-Responsive Element Binding) gene engineering in increasing plant resistance to drought and salinity stress. The method used is the Systematic Literature Review (SLR) method guided by PRISMA guidelines through a search of Scopus databases. Based on the results of a systematic literature review of 18 primary articles, the DREB gene has been shown to play an important role as an important factor in increasing plant resistance to abiotic stress. This gene works by activating various stress response genes through binding to DRE/CRT elements in the promoter region, thereby triggering cell protection mechanisms such as increased proline and soluble sugar accumulation, enhanced antioxidant enzyme activity (SOD, CAT, POD), and decreased ROS and MDA levels. The results of the study indicate that DREB gene engineering, especially through overexpression approaches and the use of inducible promoters, generally shows increased tolerance, although the response depends on the gene subtype and the genetic context of the plant. However, its effectiveness is greatly influenced by the type of DREB gene used, the genetic background of the plant, and environmental conditions. Therefore, appropriate selection of gene variants and field-scale testing remain necessary to ensure that increased tolerance of safe tests can be accompanied by sustained stability of results.